Strategi Guru dalam Mengelola Keberagaman Budaya Siswa di SMK Negeri 1 Percut Sei Tuan - Sulvi Andini Br Butar Butar; Amelia Ardan Tambunan; Lulu Hairani; Ihsana Tantri; Nurmarito Rambe (Invention: Journal Research and Education Studies, 2026)
Indonesia is a pluralistic country characterized by a high level of cultural diversity. While this diversity serves as a valuable national asset, it may also give rise to stereotypes, misunderstandings, and even horizontal conflicts within educational settings if not managed wisely. This study aims to examine teachers’ perceptions of student plurality, identify pedagogical strategies used to integrate multicultural values, and analyze the role of teachers as mediators in overcoming communication barriers caused by differences in students’ cultural backgrounds. The scope of this study focuses on heterogeneous classroom management practices at SMK Negeri 1 Percut Sei Tuan. This research employed a descriptive qualitative approach through field research. Primary data were collected through non-participant observation and in-depth interviews with key informants, including the principal, subject teachers, guidance and counseling teachers, and students. Secondary data were obtained through school documentation studies. The data analysis techniques consisted of data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The findings reveal that teachers possess a high level of critical awareness regarding multicultural realities in the classroom. The strategies implemented include creating an inclusive learning environment through strict anti-discrimination rules, integrating tolerance values into learning materials, applying collaborative learning based on heterogeneous groups, and demonstrating fair behavior as role models. These strategies were found to be effective in reducing friendship exclusivity, preventing conflict, increasing social empathy, and preparing students to live in a pluralistic society.